MANAJEMEN MUTU TERPADU DAN IMPLEMENTASINYA DALAM DUNIA PENDIDIKAN - ANA BINTARI; DAKIR DAKIR; MUSLIMAH MUSLIMAH (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2022)
The increasingly fierce competition that occurs among sellers of products and services requires each to be able to maintain and improve the quality of the products or services produced. The lack of understanding of an organization or company, whether owned by the government or private, on how to maintain public trust in the products it produces can be a crucial problem. The existence of management is very important for the sustainability of a company or organization, "Through good management, fostering cooperation becomes harmonious and harmonious as well as mutual respect and love between workers so that in the end the optimal goal will be achieved." The author uses the method of writing a literature study, with the primary data sources being literature books that discuss Total Quality Management (TQM) or Integrated Quality Management (MMT) to understand the concept of integrated quality management based on expert definitions, understand the basic principles of quality management integrated, and know the implementation of integrated quality management in educational institutions. Experts define Total Quality Management (TQM) or Integrated Quality Management (MMT) which can be concluded to refer to three basic things, namely focusing on customers, establishing good relationships with all parties and making continuous improvements. According to Cucu Supriyatna in his book Total Quality Management said that TQM programs do not always have to use TQM, in the context of education certain schools feel better by using the name The School Improvement Program. ABSTRAKSemakin ketatnya persaingan yang terjadi diantara para penjual produk dan jasa menuntut masing-masing untuk dapat mempertahankan dan meningkatkan kualitas produk atau layanan jasa yang dihasilkan. Kurangnya pemahaman suatu organisasi atau perusahaan baik milik pemerintah atau swasta tentang bagaimana menjaga kepercayaan masyarakat terhadap produk yang dihasilkan dapat menjadi permasalahan yang krusial. Keberadaan manajemen sangat penting bagi keberlangsungan sebuah perusahaan atau organisasi, “Melalui manajemen yang baik, pembinaan kerja sama menjadi serasi dan harmonis serta saling menghormati dan mencintai antar pekerja sehingga pada akhirnya tujuan optimal akan tercapai.” Penulis menggunakan metode penulisan studi literatur, dengan sumber data primer adalah buku-buku literatur yang membahas tentang Total Quality Management (TQM) atau Manajemen Mutu Terpadu (MMT) untuk memahami konsep manajemen mutu terpadu berdasarkan definisi para ahli, memahami prinsip-prinsip dasar manajemen mutu terpadu, dan mengetahui implementasi manajemen mutu terpadu di lembaga Pendidikan. Para ahli mendefinisikan Total Quality Management (TQM) atau Manajemen Mutu Terpadu (MMT) dapat disimpulkan mengacu kepada tiga hal dasar yakni berfokus kepada pelanggan, menjalin hubungan baik kepada semua pihak dan melakukan perbaikan berkesinambungan. Menurut Cucu Supriyatna dalam bukunya Total Quality Management mengatakan bahwa program-program TQM tidaklah harus selalu menggunakan TQM, dalam konteks Pendidikan sekolah tertentu merasa lebih baik dengan menggunakan nama The School Improvement Program.